2009
DOI: 10.1167/iovs.08-2642
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Reduces Inflammatory Process in a Rodent Model of Diabetic Retinopathy

Abstract: Inflammatory process, characterized by microglial activation and Müller cells dysfunction, was implicated in STZ-induced diabetic retinopathy. Baicalein treatment ameliorated inflammatory process, and therefore inhibited vascular abnormality and neuron loss in diabetic retinas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 45 publications
(43 reference statements)
5
111
0
Order By: Relevance
“…Activated microglia have also been proposed to stimulate a cycle of inflammation that recruits leukocytes, causes vascular damage, and directly induces glial dysfunction and neuronal cell death through the release of cytotoxic substances. 59 Thus, early destruction of the blood-retinal barrier in DR 60 may be driven by glial hyperactivation. 59 Exposure of microglia to inflammatory agents (including advanced glycation end products, TNF-a, IL-1, IL-6, interferon-g) results in microglial activation and production of inflammatory mediators (eg, TNF-a, IL-1, IL-6, IL-8, CCL2), 61e63 functioning in a paracrine and/or autocrine feed-forward loop to further compromise the blood-retinal barrier and elevate local retinal inflammation.…”
Section: Retinal Overexpression Of Ace2 May Suppress Proinflammatory mentioning
confidence: 99%
See 1 more Smart Citation
“…Activated microglia have also been proposed to stimulate a cycle of inflammation that recruits leukocytes, causes vascular damage, and directly induces glial dysfunction and neuronal cell death through the release of cytotoxic substances. 59 Thus, early destruction of the blood-retinal barrier in DR 60 may be driven by glial hyperactivation. 59 Exposure of microglia to inflammatory agents (including advanced glycation end products, TNF-a, IL-1, IL-6, interferon-g) results in microglial activation and production of inflammatory mediators (eg, TNF-a, IL-1, IL-6, IL-8, CCL2), 61e63 functioning in a paracrine and/or autocrine feed-forward loop to further compromise the blood-retinal barrier and elevate local retinal inflammation.…”
Section: Retinal Overexpression Of Ace2 May Suppress Proinflammatory mentioning
confidence: 99%
“…59 Thus, early destruction of the blood-retinal barrier in DR 60 may be driven by glial hyperactivation. 59 Exposure of microglia to inflammatory agents (including advanced glycation end products, TNF-a, IL-1, IL-6, interferon-g) results in microglial activation and production of inflammatory mediators (eg, TNF-a, IL-1, IL-6, IL-8, CCL2), 61e63 functioning in a paracrine and/or autocrine feed-forward loop to further compromise the blood-retinal barrier and elevate local retinal inflammation. 54,61,64 Therefore, we propose that the decline of microglial/macrophage cells in streptozotocin-ACE2 is at least partly responsible for the prevention and partial reversal of retinal vascular disease in the present study (Figure 2).…”
Section: Retinal Overexpression Of Ace2 May Suppress Proinflammatory mentioning
confidence: 99%
“…The infusion of glucose into normal volunteers and individuals with impaired glucose tolerance induces an acute increase in serum IL-18 concentrations 27 . Furthermore, it has been reported that the expression of IL-18 mRNA in the retinas of streptozotocin-induced diabetic rats as an animal model for insulin-dependent diabetes mellitus is enhanced at 24 weeks after the onset of diabetes mellitus 28 . However, to our knowledge, the effect of long-term chronic and acute hyperglycemia on IL-18 and IFN-γ production in the retina in the case of non-insulin-dependent diabetes mellitus has not yet been reported, and its elucidation is important.…”
mentioning
confidence: 99%
“…This input has originated partly from histopathologic studies that showed clustering of apparently activated microglia in the diabetic rat retina [2,3]. These initial observations have been supported in postmortem human retinas [26] and reinforced by additional histopathological studies showing that many inflammatory molecules, such as tumor necrosis factor alpha (TNF-α), can be detected in the diabetic retina, often in association with microglia [27][28][29]. The retinal expression of TNF-α has been reported to be associated with neuronal and endothelial cell death, hallmark features of the disease [12,30], and inhibition of TNF-α has demonstrated beneficial effects in the prevention of early DR [31].…”
Section: Microglia In Drmentioning
confidence: 99%